Solve for f: 6f + 9g = 3g + f

f = f equals StartFraction negative 8 g Over 3 EndFraction.
f = f equals StartFraction negative 6 g Over 5 EndFraction.
f = f equals StartFraction negative 5 g Over 6 EndFraction.
f = f equals StartFraction 12 g Over 7 EndFraction.

1 answer

To solve for f, we can simplify the equation by combining like terms:

6f + 9g = 3g + f
5f + 9g = 3g
5f = -6g
f = -6g / 5

Therefore, f = f equals StartFraction negative 6 g Over 5 EndFraction.
Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. Solve for x.StartFraction 3 x over 8 EndFraction equals 6 (1 point) Responses x = 2.25 x = 2.25 x equals negative 16 Image with
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions